New constraints on red-spiral galaxies from their kinematics in clusters of galaxies. Issue 3 (25th July 2019) - Hamabata, Akinari; Oogi, Taira; Oguri, Masamune; Nishimichi, Takahiro; Nagashima, Masahiro
ABSTRACT: The distributions of the pairwise line-of-sight velocity between galaxies and their host clusters are segregated according to the galaxy's colour and morphology. We investigate the velocity distribution of red-spiral galaxies, which represents a rare population within galaxy clusters. We find that the probability distribution function of the pairwise line-of-sight velocity v los between red-spiral galaxies and galaxy clusters has a dip at v los  = 0, which is a very odd feature, at 93 per cent confidence level. To understand its origin, we construct a model of the phase-space distribution of galaxies surrounding galaxy clusters in three-dimensional space by using cosmological N -body simulations. We adopt a two component model that consists of the infall component, which corresponds to galaxies that are now falling into galaxy clusters, and the splashback component, which corresponds to galaxies that are on their first (or more) orbit after falling into galaxy clusters. We find that we can reproduce the distribution of the line-of-sight velocity of red-spiral galaxies with the dip with a very simple assumption that red-spiral galaxies reside predominantly in the infall component, regardless of the choice of the functional form of their spatial distribution. Our results constrain the quenching time-scale of red-spiral galaxies to a few Gyr, and the radius where the morphological transformation is effective as $r \sim 0.2 \, h^{-1 } \, \rm {Mpc}$ .